Association Study of Genetic Variants in Calcium Signaling-Related Genes With Cardiovascular Diseases - Li, Sen; Jia, Zhaoqi; Zhang, Zhang; Li, Yuxin; Yan, Meihui; Yu, Tingting (Frontiers in Cell and Developmental Biology, 2021)
Background: Calcium ions (Ca2+) play an essential role in excitation-contraction coupling in the heart. The association between cardiovascular diseases (CVDs) and genetic polymorphisms in key regulators of Ca2+ homeostasis is well-established but still inadequately understood. Methods: The associations of 11,274 genetic variants located in 9 calcium signaling-related genes with 118 diseases of the circulatory system were explored using a large sample of UK Biobank (N=308,366). The clinical outcomes in electronic health records were mapped to the phecode system. Survival analyses were employed to study the role of variants in CVDs incidence and mortality. Phenome-wide association studies (PheWAS) were performed to investigate the effect of variants on cardiovascular risk factors. Results: The reported association between rs1801253 in β1-adrenergic receptor (ADRB1) and hypertension was successfully replicated, and we additionally found the blood pressure-lowering G allele of this variant was associated with a delayed onset of hypertension and a decreased level of apolipoprotein A. The association of rs4484922 in calsequestrin 2 (CASQ2) with atrial fibrillation/flutter was identified, and this variant also displayed nominal evidence of association with QRS duration and carotid intima-medial thickness. Moreover, our results indicated suggestive associations of rs79613429 in ryanodine receptor 2 (RYR2) with precordial pain and rs62420492 in triadin (TRDN) with essential hypertension. Conclusions: Multiple novel associations established in our study highlight genetic testing as a useful method for CVDs diagnosis and prevention.